![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.a) \(\left(\frac{3}{5}\right)^{15}:\left(\frac{9}{25}\right)^5=\frac{3^{15}}{5^{15}}.\frac{5^{10}}{3^{10}}=\frac{3^5}{5^5}=\left(\frac{3}{5}\right)^5\)
b)\(\left(\frac{2}{3}\right)^{10}:\left(\frac{4}{9}\right)^4=\frac{2^{10}}{3^{10}}.\frac{3^8}{2^8}=\frac{2^2}{3^2}=\left(\frac{2}{3}\right)^2\)
2.
a)\(2^x=4\Rightarrow2^x=2^2\Rightarrow x=2\)
b)\(x^3=-27\Rightarrow x^3=-3^3\Rightarrow x=-3\)
c)\(x^2=16\Rightarrow x=\pm4\)
d)\(\left(x+1\right)^2=9\Rightarrow\hept{\begin{cases}x+1=3\Rightarrow x=2\\x+1=-3\Rightarrow x=-4\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài làm:
Bài 1
a) \(\left(x-\frac{1}{2}\right)^2=0\)
\(\rightarrow\left(x-\frac{1}{2}\right)^2=0^2\)
\(\rightarrow x-\frac{1}{2}=0\)
\(\Rightarrow x=\frac{1}{2}\)
Bài 2
a) \(25^3\div5^2=\left(5^2\right)^3\div5^2=5^6\div5^2=5^4\)
b) \(\left(\frac{3}{7}\right)^{21}\div\left(\frac{9}{49}\right)^6=\left(\frac{3}{7}\right)^{21}\div\left[\left(\frac{3}{7}\right)^2\right]^6=\left(\frac{3}{7}\right)^{21}\div\left(\frac{3}{7}\right)^{12}=\left(\frac{3}{7}\right)^9\)
c) \(3-\left(\frac{-6}{7}\right)^0+\left(\frac{1}{2}\right)^2\div2=3-1+\frac{1}{4}\times\frac{1}{2}=2+\frac{1}{8}=\frac{17}{8}\)
Bài 3
a) \(9\times3^3\times\frac{1}{81}\times3^2=3^2\times3^3\times\frac{1}{3^4}\times3^2=3^3\)
b) \(4\times2^5\div\left(2^3\times\frac{1}{16}\right)=2^2\times2^5\div\left(2^3\times\frac{1}{2^4}\right)=2^7\div\frac{1}{2}=2^6\)
c) \(3^2\times2^5\times\left(\frac{2}{3}\right)^2=3^2\times2^5\times\frac{2^2}{3^2}=3^2\times\frac{2^7}{3^2}=2^7\)
d) \(\left(\frac{1}{3}\right)^2\times\frac{1}{3}\times9^2=\left(\frac{1}{3}\right)^3\times3^4=\frac{1}{3^3}\times3^4=3^1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b: =>(x-1)(x+32)>0
=>x>1 hoặc x<-32
c: =>(x+243)(x+1)<0
=>-243<x<-1
![](https://rs.olm.vn/images/avt/0.png?1311)
x-2+7 = 1.3.-9
=> x + 5 = -27
=> x = -32
4x - 1 = (-5)
=> 4x = -4
x = -1
-2x + 5 = 7
=> -2x = 2
x= -1
\(\left(x-1\right)^2-9\left(x+1\right)^2=0\)
\(\Leftrightarrow\left(x^2-2x+1\right)-9\left(x^2+2x+1\right)=0\)
\(\Leftrightarrow x^2-2x+1-\left(9x^2+18x+9\right)=0\)
\(\Leftrightarrow x^2-2x+1-9x^2-18x-9=0\)
\(\Leftrightarrow\left(x^2-9x^2\right)+\left(-2x-18x\right)+\left(1-9\right)=0\)
\(\Leftrightarrow-8x^2-20x-8=0\Leftrightarrow-\left(8x^2+20x+8\right)=0\)
\(\Leftrightarrow-\left(8x^2+16x+4x+8\right)=0\)
\(\Leftrightarrow-\left[8x\left(x+2\right)+4\left(x+2\right)\right]=0\)
\(\Leftrightarrow-\left[\left(x+2\right)\left(8x+4\right)\right]=0\)
hay (x+2)(8x+4)=0
<=>x+2=0 hoặc 8x+4=0
<=>x=-2 hoặc x=-1/2
Vậy x=-2 và x=-1/2